Keragaan Pertumbuhan dan Hasil Tanaman Jagung Manis terhadap Pemberian Dosis Pupuk Semi Organik pada Lahan Rawa Lebak - Ainor Ridha Saputera; Mahdiannoor; M. Gazali Habibi (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2013)
Maize production in Hulu Sungai Uatara Regency is still low compared to other food commodities because the land used is lebak wetland. The problem with lebak wetland is low soil fertility. One solution to improve the performance of growth and yield of corn plants is by using semi-organic fertilizers. The purpose of the study (i) was to determine the performance of growth and yield of sweet corn on doses of semi-organic fertilizer on swamp lebak (ii) to obtain the best dosage of semi-organic fertilizer that showed optimal growth and yield of sweet corn on lebak wetland. The study was carried out in the Pandulangan Village, Sungai Pandan Sub-District, Hulu Sungai Utara Regency, South Kalimantan Province, conducted in April - June 2013, using a single factor Randomized Group Design (RGD), with 5 treatment levels with 5 levels of treatment consisting of: m1 = 38 g.plot-1, m2 = 47.5 g. plot-1, m3 = 57.0 g. plot-1, m4 = 66.5 g. plot-1 and m5 = 76 g. plot-1. Each treatment consisted of 4 replications so that there were 20 experimental units. The results showed that the growth and yield of sweet corn on the application of semi-organic fertilizer on lebak wt land with the best dosage of semi-organic fertilizer was 57.0 g. plot-1 was equivalent to 300 kg. ha-1 (m3).